"It takes two to tango" : sexual health responsibilities of Kiwi heterosexual males : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology (with endorsement in Health Psychology) at Massey University, Albany, New Zealand - Henderson, Gisele (Massey University, 2018)
Within an increasingly promiscuous society, utilisation of sexual health devices is extremely important yet some individuals choose to forego preventative and protective measures resulting in pregnancy or potentially fatal sexually transmitted diseases (STDs) such as Human Papillomavirus (HPV). Globally, male HPV vaccination uptake rates were lower than that of females causing us to query why that is, what factors contribute to this and whose responsibility it is to care for sexual health. This research aimed to provide insight on the male perspective about sexual health device use to comprehend how safe sexual health decisions are negotiated. Five men underwent individual interviews and a focus group. Data was recorded, transcribed and a thematic analysis conducted. Five main themes were identified as influential factors in decisions regarding sexual health device use: Gender-role expectations and societal influences, provisional and modal educational issues, absence of efficient advertising, marketing and awareness tactics, appeal, ease of use and access to devices and justifications for where responsibilities lie. By normalising discussions regarding sexuality, social change can be generated by promoting safe sexual health. Factors influencing decision making processes, including gender-roles and external pressures, need renegotiation to include acceptance of safe sexual behaviours. Higher quality and quantity of education provision is required in a public realm to promote awareness of STDs, their consequences and prevention/protection measures available. Sexual health protective tools and services need to be easily accessible, appealing and convenient before individuals will actively prioritise sexual health. The main themes identified in this study emphasise and redirect attention toward improvements required within future sexual health programme implementation to improve health outcomes. The themes established identify influential factors that require change in order to remove current barriers to care and to promote healthy sexual behaviours in place of risky ones.
Keywords: Men -- New Zealand -- Sexual behavior; Men's health services -- New Zealand; Male reproductive health services -- New Zealand; Sexual health -- New Zealand; Sex role -- New Zealand; Sex instruction -- New Zealand; Masculinity -- New Zealand